(untitled) (The Review of Diabetic Studies, 2025)
Environmental, Social, and Governance (ESG) investing has gained significant attention as investors increasingly seek to align financial returns with ethical, social, and environmental considerations. In India, ESG funds are emerging as a promising investment avenue; however, regional-level investor behavior remains underexplored. This study examines the factors influencing investors’ decision-making to invest in ESG funds in Telangana State. Primary data were collected from 200 individual investors using a structured questionnaire. Statistical tools such as descriptive analysis, factor analysis, and multiple regression analysis were employed to analyze the data. The findings reveal that governance transparency, environmental concern, financial performance expectations, and ESG awareness significantly influence ESG investment decisions, while risk perception does not have a significant impact. The study offers valuable insights for asset management companies, policymakers, and financial advisors to promote sustainable investing in Telangana State.